EIB Complaints Mechanism Report 2020 - European Investment Bank (European Investment Bank, 2021)
Any concerns about an EIB Group activity or project? The Complaints Mechanism listens to citizens and ensures their voice can be heard. Have a look at its Activity Report for 2020. 2020 was a particularly challenging year amid the COVID-19 pandemic crisis. The EIB Group Complaints Mechanism (EIB-CM) had to find innovative ways to not only handle complaints but also interact with its key stakeholders. In 2020, the EIB-CM registered 77 new cases, handled 137 cases and closed 94 of them. The number of outstanding complaints at year-end has continued to decrease, from 89 in 2018 to 60 in 2019 and to 43 in 2020. The EIB-CM managed to close most long-overdue cases during the year. A number of highly complex cases were closed in 2020, including Nenskra HPP (Georgia), Réseau Ferroviaire Rapide (Tunisia) and Cairo Metro Line (Egypt). The key achievements are reflected in the annually published Complaints Mechanism Activity Report, which gives an overview of how through its actions the EIB Group remains accountable to the public.